2019
DOI: 10.1016/j.pmedr.2019.100841
|View full text |Cite
|
Sign up to set email alerts
|

The association of financial incentives for low density lipoprotein cholesterol reduction with patient activation and motivation

Abstract: There is growing interest in using financial incentives for patients to improve medication adherence, but few studies have evaluated whether financial incentives are associated with patients' activation and motivation. We analyzed survey data collected as part of a randomized clinical trial conducted from 2011 to 2014 of four financial incentive interventions to reduce low density lipoprotein cholesterol (LDL-C) among patients at risk for atherosclerotic cardiovascular disease. The main trial included 1503 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Monetary payment can induce short-term (and sometimes longer-term) health behavior changes, such as smoking cessation and healthy eating 45,46 but impact on medical conditions requiring long-term medication use is mixed [47][48][49][50][51][52] For example, use of lotteries increased short-term warfarin adherence, but the effect disappeared after the incentive was removed. 24 Sustained benefit in chronic disease care may require continued payments (particularly in populations with many competing demands and challenges), or additional interventions to promote patient attribution of behavior change to internal motivation, 26 or to influence clinician behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Monetary payment can induce short-term (and sometimes longer-term) health behavior changes, such as smoking cessation and healthy eating 45,46 but impact on medical conditions requiring long-term medication use is mixed [47][48][49][50][51][52] For example, use of lotteries increased short-term warfarin adherence, but the effect disappeared after the incentive was removed. 24 Sustained benefit in chronic disease care may require continued payments (particularly in populations with many competing demands and challenges), or additional interventions to promote patient attribution of behavior change to internal motivation, 26 or to influence clinician behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that economic measures at the national level have an effect on population health [57]. However, another study has shown that economic incentives are not always related to people’s motivation to improve their own health [58]. Thus, there may be limits to the economic measures at the national level.…”
Section: Discussionmentioning
confidence: 99%
“…Results of several studies using a lottery incentive program (“regret lottery”) approach, whereby participants are encouraged to undertake healthy behaviors through the desire to avoid regret over losing financial incentives, have been promising [ 10 , 11 ]. However, other interventions tested have been negative [ [12] , [13] , [14] ] or effective only in limited subgroups [ 15 ]. Further, with few exceptions [ 16 ], whether these incentives translate to sustainable behavior change in vulnerable populations is unclear.…”
Section: Background and Rationalementioning
confidence: 99%